Life cycle assessment of the handling and transportation of palm oil, palm olein and palm stearin / Fauziah Arshad - Fauziah, Arshad (2016)
Transportation is an important component of the palm oil supply chain and it is one of the main sources of greenhouse gas (GHG) arising from the use of fossil fuel. The scope of the study is to determine the environmental impacts of the refined bleached and deodorized (RBD) palm oil and its fractionated products namely palm olein and palm stearin along the palm supply chain which is from cradle-to-gate i.e. from the transportation of oil palm fruit bunches from the ‘mother palm’ to the seed producers, the transportation of the germinated seeds to the nurseries, the transportation of seedlings from nurseries to oil palm plantations, the transportation of fresh fruit bunches (FFB) from plantations to mills, the transportation of crude palm oil (CPO) from mills to refineries and finally the transportation of refined, bleached and deodorized (RBD) palm oil, RBD palm olein and RBD palm stearin from refineries/fractionation plants to ports and retailers by using the Life Cycle Assessment (LCA) approach. The Life Cycle Inventory (LCI) on the energy consumption and GHG emission is based on site-specific data collected from questionnaires sent to nurseries, plantations, mills and refineries throughout Malaysia including Sabah and Sarawak and calculated using emission factors. The LCI analysis on the energy consumption based on the production of 1 tonne RBD palm oil indicated that transportation of FFB from plantation to palm oil mill were the highest followed by transportation of RBD palm olein from refinery to retailers and CPO from mills to refineries at 197.12 MJ, 192.78MJ and 151.50 MJ respectively. Based on the production of 1 tonne RBD palm oil, the GHG emissions during the transportation of FFB from plantations to mills and transportation of CPO from mills to refineries were 21.94 kg CO2 eq. and 20.86 kg CO2 eq. respectively. The weighted results of the life cycle impact assessment (LCIA) showed that the most significant environmental impacts from this study were contributed by the impact categories in the following order: fossil fuel, respiratory in-organics, acidification/eutrophication and climate change. The environmental impacts were highest during the transportation of FFB from the oil palm plantations to palm oil mills followed by the transportation of CPO from the mills to refineries. Mitigations for improvements include using other modes of transportation such as rail to transport the FFB and CPO and improved infrastructure for more pipelines to export the refined palm oil.